Agronomic performance of popcorn genotypes in Northern and Northwestern Rio de Janeiro State - doi: 10.4025/actasciagron.v35i1.15694 - Thiago Rodrigues da Conceição Silva; Antonio Teixeira do Amaral Júnior; Leandro Simões Azeredo Gonçalves; Liliam Silvia Candido; Cassio Vittorazzi; Carlos Alberto Scapim (Acta Scientiarum. Agronomy, 2012)
Three populations of popcorn from the Universidade Estadual do Norte Fluminense Darcy Ribeiro recurrent selection program (cycles C3, C4 and C5 from UNB2U), five simple hybrids provided by the Universidade Estadual de Maringá breeding program, five varieties (BRS Angela, UFVM-2 Barão de Viçosa, Viçosa, Beija-Flor and SAM) and three commercial hybrids (Zelia, Jade and IAC 112) were evaluated in five environments for their potential to be registered by the MAPA and recommended to producers in Northern and Northwestern Rio de Janeiro State. The experiment was arranged in a randomized block design, with three replications. The two main economic traits of the crops, grain yield (GY) and popping expansion (PE), were assessed. In the joint analysis of variance, significant differences were observed using the F test for the GY and PE traits. Regarding the genotype x environment interaction, only the GY was significant, thus revealing that the cultivar behavior varies according to the environment. The Pi statistics and the results for those traits showed that UNB2U-C5 and hybrid P1 x P7 have the potential to be recommended as new alternatives for producers in the region.